How fortunate we are indeed to have such a poet on these shores’: Shakespeare, Monty Python, and the Tradition of the Wise Fool - González-Campos, Miguel Ángel (Rowman & Littlefield, 2014)
This paper purports to explore the presence of William Shakespeare in Monty Python’s creations, a presence which is not limited to the explicit allusions to the Bard himself or to the characters, the events or even the criticism of his plays. Monty Python also consciously appropriates some of the most defining Shakespearean structural devices such as the anachronistic use of history, the practice of cross-dressing, the unorthodox approach to the conventions of the medium, the self-awareness of the artistic artefact which represents a constant reminder of the artificial nature of the work audiences are contemplating, the collapse of the rigid boundaries between high and low culture, etc. In this sense special attention will be paid to one of the most interesting and fruitful Shakespearean influences on Monty Python that is the role of the wise fool not only in their works but also in themselves as creators. Significantly enough the Pythons worked for years as a kind of “licensed fools” under the patronage of the official cultural authority of the BBC like the medieval courtly fools or even like Shakespeare himself as a member of the King’s Men. Although the archetype of the wise fool is not a creation by Shakespeare (its tradition dates back from classical writers such as Aesop or Cicero to Erasmus’s The Praise of Folly through Tudor moral plays and other medieval literary works and popular celebrations) it was the Bard who gave the role of the fool the reinvigorating force of a universal character as he appears in plays such as King Lear, Twelfth Night or As You Like It. The Shakespearean wise fool often calls into question the conventional view of reality and invites other characters to look at it from a different angle apparently absurd but on a deeper level hugely meaningful. It is precisely this tradition which inspires and informs most of Monty Python’s works.
Permission is granted non-exclusive and no fee to include the material cited below in an institutional repository upon the following conditions: That the material has already been published by an imprint of The Rowman & Littlefield Publishing Group and that publication was at least 18 months ago; That full acknowledgement is made of the original publication stating the specific material reused [pages, figure numbers, etc.], [Title] by/edited by [Author/editor], [year of publication], reproduced by permission of Rowman & Littlefield [link to the R&L website]; That copyright is emphasized by including the following statement: All rights reserved. Please contact the publisher for permission to copy, distribute or reprint. In the case of joint-authored works, it is the responsibility of the authors to obtain permission from co-authors for the work to be included in the repository; and that the material is not distributed under any kind of Open Access style licenses (e.g. Creative Commons) which may affect the License with The Rowman & Littlefield Publishing Group.
Keywords: Shakespeare, William (1564-1616) - Crítica e interpretación; Monty Python; Shakespeare; Adaptation